Perturbations in the gene regulatory pathways controlling mitochondrial energy production in the failing heart - Aubert, Gregory (2012)
The heart is an omnivore organ that requires constant energy production to match its functional demands. In the adult heart, ATP production occurs mainly through mitochondrial fatty acid and glucose oxidation. The heart must constantly adapt its energy production in response to changes in substrate supply and work demands across diverse physiologic and pathophysiologic conditions. The cardiac myocyte maintains a high level of mitochondrial ATP production through a complex transcriptional regulatory network that is orchestrated by the members of the peroxisome proliferator-activated receptor gamma coactivator-1 (PGC-1) family. There is increasing evidence that during the development of cardiac hypertrophy and in the failing heart, the activity of this network, including PGC-1, is altered. This review summarizes our current understanding of the perturbations in the gene regulatory pathways that occur during the development of heart failure. An appreciation of the role this regulatory circuitry serves in the regulation of cardiac energy metabolism may unveil novel therapeutic targets aimed at the metabolic disturbances that presage heart failure.